The Impact of Socioeconomic Factors on Knowledge, Attitudes, and Practices of Dog Owners on Dog Rabies Control in Thailand - Premashthira, Sith; Suwanpakdee, Sarin; Thanapongtharm, Weerapong; Sagarasaeranee, Onpawee; Thichumpa, Weerakorn; Sararat, Chayanin; Wiratsudakul, Anuwat (Frontiers in Veterinary Science, 2021)
Rabies is a deadly zoonotic disease responsible for almost six thousand deaths each year, especially in Africa and Asia including Thailand. Dogs are the major reservoirs for rabies virus in these settings. This study thus used the concept of knowledge, attitudes, and practices (KAP) to identify socioeconomic factors that contribute to the differences in the canine rabies occurrences in high and low-risk areas which were classified by a Generalized Additive Model (GAM). Multistage sampling was then applied to designate the study locations and a KAP-based questionnaire was used to retrieve data and relevant perspectives from the respondents. Based on the responses from 476 participants living across four regions of Thailand, we found that the knowledge of the participants was positively correlated with their behaviors but negatively associated with the attitudes. Participants who are male, younger, educated at the level of middle to high school, or raising more dogs are likely to have negative attitudes but good knowledge on rabies prevention and control whereas farmers with lower income had better attitudes regardless of their knowledge. We found that participants categorized as younger, living in the high-risk areas, with higher education or higher income are willing to pay more for the rabies vaccines. Public education is a key to change dog owners’ behaviors. Related authorities should constantly educate people on how to prevent and control rabies in their community. Our findings should be applicable to other countries with similar socioeconomic statuses.